Coerced syphilis self-testing among men who have sex with men: a nationwide cross-sectional study in China - Zhao, Peizhen; Shi, Yijia; Wang, Cheng (BMC infectious diseases, 2022)
Syphilis testing uptake remains low among men who have sex with men (MSM) in many low-and middle-income countries. Syphilis self-testing is an efficacious approach on increasing syphilis testing coverage. However, one unintended consequence is the syphilis self-testing coercion from others (including partners, healthcare providers, friends, etc.). This study aimed to examine the prevalence, pattern and correlates of coerced syphilis self-testing among MSM in China. A nationwide online cross-sectional study was conducted from 14 to 28 July 2018. Sociodemographic characteristics, sexual behaviors and coerced syphilis self-testing variables were collected through a questionnaire that targeted MSM in China. Multivariable logistic regression was used to explore associated factors with syphilis self-testing coercion. Overall, 174 MSM were recruited in this study, 31 men (17.8%) reported ever experiencing syphilis self-testing coercion. The most common types of coercion before syphilis self-testing were verbal abuse (38.7%, 12/31) and threatening to end a relationship (38.7%, 12/31). After obtaining the self-test results, men were mostly subjected to end a relationship (45.2%, 14/31) and threaten of violence (35.5%, 11/31). Multivariable logistic regression indicated that men who used condoms inconsistently in the past three months, ever used substances before or during sex, ever had group sex with males and commercial sex were more likely to experience syphilis self-testing coercion. Coerced syphilis self-testing was prevalent among MSM in China. Innovative intervention to reduce coerced syphilis self-testing is necessary among MSM in China.